تسجيل النوع السمكي Pterois miles (Osteichthyes:Scorpaenidae) للمرة الأولى في الساحل السوري: تأكيد ظهوره في الحوض الشرقي للبحر الأبيض المتوسط - علي, مالك; القصيري, حسن; سعد, أديب; رينو, كريستيان; كابيبي, كريستيان (Latakia University Journal -Biological Sciences Series, 2017)
This paper aimed to present the first record of Pterois miles (Bennet, 1828) off the Syrian coast (Eastern Mediterranean). Two specimens (159; 206 mm SL) were captured in Syrian waters between Lattakia and Jableh in 28th September 2015 and 10th December 2015. This first record of common lionfish Pterois miles in the Syrian coast could confirm the occurrence of this species in the Levant Basin (eastern Mediterranean). This is the fifth record of the species reported to date in the region. These records are not sufficient to state that the species is substantially established in the area, but investigations are rapidly needed to avoid unfavorable consequences on local environment and economy.هدف هذا المقال لعرض تسجيل سمك الأسد الشائع Pterois miles (Bennet, 1828) للمرة الأولى في الساحل السوري (شرق البحر المتوسط). إذ تم في يومي 28 أيلول 2015 و10 وكانون الأول 2015 اصطياد عينتين (159، 206 ملم طول قياسي) من النوع المذكور في المياه البحرية السورية بين مدينتي اللاذقية وجبلة. إن تسجيل هذا النوع للمرة الأولى في المياه السورية يؤكد استمرار ظهوره في الحوض الشرقي للمتوسط. ويعد هذا التسجيل، التسجيل الخامس في المنطقة حتى تاريخه، غير أنه لا يمكن اعتبار هذه التسجيلات كافية لإثبات انتشار هذا النوع السمكي بشكل فعلي في المنطقة، وبالتالي لابد من إجراء تحقيقات سريعة احترازية لتجنب النتائج السلبية البيئية والاقتصادية المحتملة من انتشاره في المنطقة.